Activity Theory and Analyzing Learning in Simulations. (April 2015) - Battista, Alexis
Purpose . The purpose of this theoretical article is to demonstrate howactivity theory, a neo-Vygotskian sociocultural theory, can be used to analyze learning during simulation-based activities. Background . Simulations are complex, dynamic environments that evolve and change throughout implementation. Moreover, simulations simultaneously supportmultiple participants' assigned differentroles . This means that the learning within them is oftenco-constructed, rather than individually derived. These characteristics complicate understanding the learning within them. Method . This article presents a summary of the basic tenants ofactivity theory (AT ), followed by a worked example to demonstrate how AT can be used as an analytic lens to generate rich description and analysis of participant activities as embedded in a complex dynamic simulation. Conclusions . Activity theory can be used as atheoretical lens in order to account for how participants partake in simulation-based learning contexts, which supports the rich description and analysis of how participants accomplish their goals.